Concomitant radio-chemotherapy for larynx preservation - Crispino, Sergio (Radiology and oncology (Ljubljana), 1997)
Background: A pilot multicentric study of concomitant radio-chemotherapy was performed to evaluate the feasibility, the toxicity and larynx preservation rate in patients with previously untreated, resectable laryngo-pharyngeal squamous cell carcinoma, otherwise requiring laryngectomy +- pharyngectomy. Materials and methods. Forty-two patients entered the study: radiotherapy was planned to a tumour dose of 70 Gy and chemotherapy was applied concomitantly, consisting of Cisplatinum and 5-Fluorouracil (bolus) or Carboplatinum and 5-Fluorouracil (continuous infusion) combination repeated every 3 weeks. In all but complete responders laryngestomy +- pharyngectomy and/or neck dissection was performed for residual disease. Results: Toxicity was mild and no drug related deaths occurred. Complete response rate was 81% and, after salvage surgery, 93% of patients were considered disease free. After a median follow-up of 38 months, 53% of patients were alive and of these 88% with larynx preserved. Conclusion: Concomitant radiochemotherapy seems to be a feasible strategy with acceptable toxicity for patients with laryngo-pharyngeal squamous cell carcinoma, otherwise eligible for total laryngectomy.
Keywords: Drug therapy; Laryngeal neoplasms; Laryngectomy; Radiotherapy; Treatment outcome